On the Move: Evading Distributed Denial-of-Service Attacks. - Stavrou, Angelos; Fleck, Daniel; Kolias, Constantinos (Computer (00189162), 2016)
A proposed moving-target defense against DDoS attacks repeatedly shuffles client-to-server assignments to identify and eventually quarantine malicious clients.